2011
DOI: 10.3989/scimar.2011.75n1189
|View full text |Cite
|
Sign up to set email alerts
|

Faunistic assemblages of a sublittoral coarse sand habitat of the northwestern Mediterranean

Abstract: SUMMARY:The sublittoral megabenthic assemblages of a northwestern Mediterranean coarse sandy beach exploited for the bivalve Callista chione were studied. The spatial and bathymetric variability of its distinctive faunal assemblages was characterised by quantitative sampling performed with a clam dredge. The taxa studied were Mollusca Bivalvia and Gastropoda, Crustacea Decapoda, Echinodermata and Pisces, which accounted for over 99% of the total biomass. Three welldifferentiated species assemblages were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Baeta and Ramón (2013) reported that this bivalve was one of the main preys of the seastar species of the genus Astropecten in the western Mediterranean Sea, and they are also consumed by other invertebrates such as the gastropod Hexaplex trunculus (Morton et al 2007) and the cephalopod Octopus vulgaris (Fiorito and Gherardi 1999). C. chione is commercially exploited and consumed in Portugal and the Mediterranean Sea (Gaspar et al 2001, Tirado et al 2002, Metaxatos 2004, Pubill et al 2011, Baeta et al 2014 where it is captured with small boats using different types of artisanal dredges. One of the main coastal shellfish areas where a major clam fishery targeted the smooth clam is the Maresme coast, located to the northeast of Barcelona (NW Mediterranean Sea).…”
Section: Introductionmentioning
confidence: 99%
“…Baeta and Ramón (2013) reported that this bivalve was one of the main preys of the seastar species of the genus Astropecten in the western Mediterranean Sea, and they are also consumed by other invertebrates such as the gastropod Hexaplex trunculus (Morton et al 2007) and the cephalopod Octopus vulgaris (Fiorito and Gherardi 1999). C. chione is commercially exploited and consumed in Portugal and the Mediterranean Sea (Gaspar et al 2001, Tirado et al 2002, Metaxatos 2004, Pubill et al 2011, Baeta et al 2014 where it is captured with small boats using different types of artisanal dredges. One of the main coastal shellfish areas where a major clam fishery targeted the smooth clam is the Maresme coast, located to the northeast of Barcelona (NW Mediterranean Sea).…”
Section: Introductionmentioning
confidence: 99%